Retour sur un paradoxe de la normativité éducative - Henri Louis Go (Recherches en Éducation)
The individual cannot really take place as subject in a community, that in proportion of capacities to act built for him and with him, capacities which result necessarily from his understanding of the reasons for being corresponding standards. For every individual, to act of itself it is at first and paradoxically to act according to the standards of a given culture: whatever is the context in which acts such or such individual, he acts necessarily according to habits and conditioning appropriate for a given group, and in all the educational forms, we accustom the children to react according to a system organizing taxinomique all their social lived. Classifications grace of which we think, are always supplied to us already quite made. The attempts not to think any more on rails, not to be thought any more by institutions and to escape their control risk hardly to be that an illusion, so much they seem to lead in good logic to the appearance of new institutions that produce new classifications, which are developing new styles of reasoning. The issue is whether the child can learn to engage itself in terms of values and common ideas that are transmitted in order to enter a regime of collective meanings, but becoming progressively about a normative institutions.